Integrating STEM and Global Citizenship in Southeast Asia: A Comparative Study of Student Character Values in Elementary Schools - Aulia Ihza Cahya; Dede Trie Kurniawan; Yunus Abidin (Universitas Negeri Malang, 2025)
Abstract: This study aims to analyze and compare the integration of STEM (Science, Technology, Engineering, and Mathematics) education and global citizenship in the development of student character values in elementary schools across Southeast Asia. The research method employed is a descriptive comparative study, involving interviews with 18 informants, including school principals, teachers, and students from elementary schools in Indonesia, the Philippines, and Thailand. The findings indicate differences in student understanding and engagement related to STEM education and global citizenship, as well as its impact on student character values. Schools that successfully integrated both aspects showed significant improvements in student character values. The findings of this research are expected to provide recommendations for the development of educational policies in the Southeast Asian region. Abstrak: Penelitian ini bertujuan untuk menganalisis dan membandingkan integrasi pendidikan STEM (Sains, Teknologi, Teknik, dan Matematika) dan kewarganegaraan global dalam pengembangan nilai-nilai karakter siswa di sekolah dasar di Asia Tenggara. Metode penelitian yang digunakan adalah studi deskriptif komparatif, melibatkan wawancara dengan 18 informan, termasuk kepala sekolah, guru, dan siswa dari sekolah dasar di Indonesia, Filipina, dan Thailand. Hasil penelitian menunjukkan perbedaan dalam pemahaman dan keterlibatan siswa terkait pendidikan STEM dan kewarganegaraan global, serta dampaknya terhadap nilai-nilai karakter siswa. Sekolah yang berhasil mengintegrasikan kedua aspek tersebut menunjukkan peningkatan signifikan dalam nilai-nilai karakter siswa. Temuan penelitian ini diharapkan dapat memberikan rekomendasi untuk pengembangan kebijakan pendidikan di kawasan Asia Tenggara.